NARRATIVE REVIEW: PERAN SERTIFIKASI HALAL DALAM PRODUK BERBAHAN DASAR AYAM SECARA HUKUM SYARI’AT ISLAM - Budiana, Budiana; Rahman, Budi; Fathurrohim, Muhammad Faizal; Nurhayati, Rika; Bakar, Bakar; Fadilah, Ilham (International Journal Mathla’ul Anwar of Halal Issues, 2025)
Halal labels in the use of processed chicken products are very important, because in the period 2020 - 2025 there have been many chicken-based food products as food variations both in the form of franchises and other processed products. This study uses a literature method to validate how chicken-based food products can get halal certification. The results of the study show that a product that is halal certified is through a processing process using Islamic law. Halal and good animals are also determined during the slaughtering and processing process. The audit includes several things including; checking the data sent, checking the production process, laboratory, packaging, storage, transportation, distribution, marketing, presentation to halal certification.